Plant-microbial linkages underpin carbon sequestration in contrasting mountain tundra vegetation types. (February 2022) - Gavazov, Konstantin; Canarini, Alberto; Jassey, Vincent E.J.; Mills, Robert; Richter, Andreas; Sundqvist, Maja K.; Väisänen, Maria; Walker, Tom W.N.; Wardle, David A.; Dorrepaal, Ellen
Abstract: Tundra ecosystems hold large stocks of soil organic matter (SOM), likely due to low temperatures limiting rates of microbial SOM decomposition more than those of SOM accumulation from plant primary productivity and microbial necromass inputs. Here we test the hypotheses that distinct tundra vegetation types and their carbon supply to characteristic rhizosphere microbes determine SOM cycling independent of temperature. In the subarctic Scandes, we used a three-way factorial design with paired heath and meadow vegetation at each of two elevations, and with each combination of vegetation type and elevation subjected during one growing season to either ambient light (i.e., ambient plant productivity), or 95% shading (i.e., reduced plant productivity). We assessed potential above- and belowground ecosystem linkages by uni- and multivariate analyses of variance, and structural equation modelling. We observed direct coupling between tundra vegetation type and microbial community composition and function, which underpinned the ecosystem's potential for SOM storage. Greater primary productivity at low elevation and ambient light supported higher microbial biomass and nitrogen immobilisation, with lower microbial mass-specific enzymatic activity and SOM humification. Congruently, larger SOM at lower elevation and in heath sustained fungal-dominated microbial communities, which were less substrate-limited, and invested less into enzymatic SOM mineralisation, owing to a greater carbon-use efficiency (CUE). Our results highlight the importance of tundra plant community characteristics (i.e., productivity and vegetation type), via their effects on soil microbial community size, structure and physiology, as essential drivers of SOM turnover. The here documented concerted patterns in above- and belowground ecosystem functioning is strongly supportive of using plant community characteristics as surrogates for assessing tundra carbon storage potential and its evolution under climate and vegetation changes. Graphical abstract: Image 1 Highlights: A mechanistic field experiment testing above- and belowssground linkages in tundra. Tundra vegetation types determine belowground ecosystem composition and functioning. Photosynthetic inputs drive soil microbial biomass and physiology via CN stoichiometry. Fungal dominance in tundra soils boosts microbial carbon use efficiency and turnover. Tundra vegetation as a consistent proxy to soil carbon and nitrogen fluxes and stocks.